Hubungan Upaya Pencegahan Terduga Tuberkulosis Dengan Temuan Kasus Tuberkulosis Di Provinsi Daerah Istimewa Yogyakarta (DIY) - Driana Desy Purwiningsih; Vike Mei Diastutik; Siti Masnunah (Pascasarjana Universitas Jember, 2022)
The Case Notification Rate (CNR) figure for all TB cases describes the number of new patients of all types (Pulmonary TB, Extra Pulmonary and Pediatric TB) found and recorded among 100,000 residents. Meanwhile, the CNR New cases of BTA TB (+) describe the number of new positive BTA TB patients found and recorded among 100,000 residents. TB CNR in 2020 and 2021 decreased compared to 2019, from 145.18 per 100,000 population in 2019 to 103.45 per 100,000 population in 2020 and 115.73 per 100,000 population in 2021. This study aims to determine the relationship between efforts to prevent suspected Tuberculosis with the findings of Tuberculosion cases in DIY Provinces This study is an analytical study with a cross-sectional approach. The results of this study are significant the relationship between efforts to prevent suspected Tuberculosis with the findings of Tuberculosis cases in DIY Province is 0.007 below 0.05. So it can be concluded that there is a relationship between efforts to prevent suspected Tuberculosis with the findings of Tuberculosis cases in DIY Province. Optimizing the tracking of cases of missing out to prevent drop outs and patients from moving in collaboration with community cadres, Sweeping TB case data in the Service to reduce unreported data and Increasing the role of Independent Peaktek Doctors and Pratama Clinics in the DOTS TB Program by activating the Distict Public Privat Mix (DPPM) in Yogyakarta City.